2018
DOI: 10.33805/2638-8073.109
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anxiety and Depression among Mothers of Newborns Admitted to Neonatal Intensive Care Units in Gaza Strip

Abstract: Objective: To determine the prevalence and level of anxiety and depression among mothers of newborns admitted to neonatal intensive care units in Gaza Strip. Methods: It is a cross-sectional study including 195 mothers who’s their neonates has been admitted to NICU at the three governmental hospitals in Gaza Strip between November 2017 to September 2018. Two psychological tests were applied, the Hamilton Anxiety Rating Scale and the Beck Depression Inventory. Collected data include sociodemographic profile fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…The present study findings were consistent with the findings of studies done by Salah M, et al [3] found that 24.6% of the mothers were primi parous. Subhashini L, et al [11] revealed that majority of the mothers (86.6%) were under 25 years.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The present study findings were consistent with the findings of studies done by Salah M, et al [3] found that 24.6% of the mothers were primi parous. Subhashini L, et al [11] revealed that majority of the mothers (86.6%) were under 25 years.…”
Section: Discussionsupporting
confidence: 94%
“…Admission of a neonate to the intensive care unit would be unexpected and nervous for their mothers [2]. Salah M et al [3] have found 50.8% of mothers of preterm and low birth weight infants admitted in the NICU in Gaza Strip of Palestine had severe to very severe symptoms of anxiety, 38.5% of mothers had severe to very severe symptoms of depression. Hospitalizing the newborn is a key stressful event for all the relations especially the mother.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fathers typically experienced fewer depressive symptoms (ES, 0.12; 95% CI, 0.03–0.22; I 2 =85.6%; P <0.00) than mothers (ES, 0.31; 95% CI, 0.24–0.38; I 2 =91.5%; P <0.001) whose newborns were in the NICU [ 6 , 8 , 14 , 17 - 19 , 35 , 37 , 39 - 41 , 43 ]. An overall subgroup analysis revealed that 28% of parents were depressed about NICU admissions (ES, 0.28; 95% CI, 0.21–0.35; I 2 =94.6%; P <0.001) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Biological and environmental factors can trigger anxiety and/or depression in the puerpery. In this context, the Neonatal Intensive Care Unit, as an area of care for vulnerable newborns who need specific and continuous care, can be an element that triggers emotional distress (2) .…”
Section: Introductionmentioning
confidence: 99%